Association Between PON1 (L55M and Q192R) Genetic Polymorphism and Recurrent Pregnancy Loss in North Indian Women Exposed to Pesticides - Shyam Pyari Jaiswar; Apala Priyadarshini; Apurva Singh; Mohd Kalim Ahmad; Sujata Deo; Pushpa Sankhwar (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2022)
Abstract Objective The aim of the present study was to examine the relation between the PON1 polymorphisms and recurrent pregnancy loss (RPL). Methods In a cross-sectional study, blood samples were collected from 100 females. DNA was extracted and PON1 genotypes were determined by polymerase chain reaction (PCR) amplification. Results Regarding PON1 L55M, the mutated allele (M) frequency was found in 70.5% in RPL and in 53.5% in controls; theMallele was significantly associated with an increased risk of RPL (adjusted odds ratio [ORadj]=2.07; 95% confidence interval [CI]; p<0.001). However, regarding PON1 Q192R, the R mutated allele frequency was found in 28.5% in RPL and in 33% in controls. The R allele did not show any risk for RPL (ORadj 0.81; 95%CI; p=0.329). Conclusion The present study suggests that there is an effect of genetic polymorphism on RPL and provides additional evidence that combines with the growing information about the ways in which certain PON1 genotypes can affect the development of the fetus in the uterus.